Molecular DNA studies of three Aquilaria species in Malaysia - Lee, Shiou Yih (2011)
There are five Aquilaria species reported from Malaysia: A. beccarania, A. hirta, A. malaccensis, A. microcarpa and A. rostrata. Although A. malaccensis is the most well-known gaharu-producing species which supplies bulk trades domestically and internationally, its genetic information is lacking. Establishment of Aquilaria plantation and sustainable gaharu production can be seen as an effort to diversify the gaharu industry without threatening the conservation effort in nature. Hence, the understanding of genetic diversity and variation of the different species is essential for the establishment of effective conservation practices for Aquilaria species in Malaysia. In this study, Random Amplified Polymorphic DNA (RAPD) markers were used to measure genetic diversity of A. hirta, A. malaccensis and an incomplete known species, Aquilaria sp.1. Initially, 60 RAPD primers were analyzed, yielding 23 RAPD showing clear and reproducible polymorphism results. A total of 368 bands were scored. Multi-populations Descriptive Statistics revealed that 333 (90.49%) polymorphic bands were found at species level: A. malaccensis had 107 (29.08%)bands, A. hirta had 56 (15.22%), and Aquilaria sp.1 had 11 (2.99%), for the percentage of polymorphic loci in a species. Nei’s unbiased measurement indicates moderate similarities among species in this study. Out of the 23 RAPD primers,OPA02, OPA08 and OPB06 were found specific to A. hirta, OPA05 to Aquilaria sp.1, and OPA09 to A. malaccensis. PCR amplicons were cloned and sequenced to develop highly specific primers. Based on the sequence information, Sequence Characterized Amplified Region (SCAR) primers were designed. In Aquilaria sp.1, the SCAR marker OPA05AS yielded a 637 bp band. In A. hirta, OPA02AH yielded a 955 bp band, a SCAR marker named OPA08AH yielded a 866 bp band, and OPB06AH yielded a 826 bp band. In A. malaccensis, OPA09AM yielded a 566 bp band. These results showed successful detection in genetic variation among Aquilaria species in Malaysia using RAPD markers. SCAR markers were also successfully developed to help in distinguishing these three Aquilaria species. In classical identification, reproductive parts are most important for species identification. However this is not easily done when examining their vegetative parts such as the leaf, branch and bark. In this study, general descriptions of three different Aquilaria species were recorded, crosschecked with previous literatures and botanical records: A. hirta through their heavily pubescent, large-sized leaves, A. malaccensis through elliptic-lanceolate shape leaves and Aquilaria sp.1 from the existence of strongly raised lateral veins below the leaves. In conclusion, the identification of Aquilaria species with higher level of confidence can be achieved by performing both botanical observations and molecular authentication with the aid of molecular markers. Molecular information can support species identification for Aquilaria species even with the absence of their reproductive parts. This will help in reducing the occurrence of species misidentification caused by phenotype changes due to environment factors. These results are useful information for conservation and molecular breeding purposes in the future.